1969
DOI: 10.1085/jgp.54.3.310
|View full text |Cite
|
Sign up to set email alerts
|

The Ventral Photoreceptor Cells of Limulus

Abstract: The ventral photoreceptors of Limulus polyph,mus are unipolar cells with large, ellipsoidal somas located long both "lateral olfactory nerves." As a consequence of their size and location, the cells are easily impaled with microelectrodes. The cells have an average resting potential of --48 my. The resting potential is a function of the external concentration of K. When the cell is illuminated, it gives rise to the typical "receptor potential" seen in most invertebrate photoreceptors which consists of a transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
88
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(111 citation statements)
references
References 29 publications
23
88
0
Order By: Relevance
“…1977 by this method). The average capacitance as determined from five cells was 4.2 +-1.4 x 10 -9 F, a value in reasonable agreement with the results of Millecchia and Mauro (1969a). This implies a total membrane area of 4.2 × 10 -3 cm ~.…”
Section: Surface Density Charge Movement and Thermal Isomerization supporting
confidence: 87%
See 1 more Smart Citation
“…1977 by this method). The average capacitance as determined from five cells was 4.2 +-1.4 x 10 -9 F, a value in reasonable agreement with the results of Millecchia and Mauro (1969a). This implies a total membrane area of 4.2 × 10 -3 cm ~.…”
Section: Surface Density Charge Movement and Thermal Isomerization supporting
confidence: 87%
“…This implies a total membrane area of 4.2 × 10 -3 cm ~. If the photoreceptor ~¢ere not invaginated, its surface area would be 5 × 10 -4 cm 2 (Millecchia and Mauro, 1969a). Thus most of the plasma membrane in the ventral photoreceptor is in the microvilli.…”
Section: Surface Density Charge Movement and Thermal Isomerization mentioning
confidence: 99%
“…4C, n ϭ 4). These responses are indistinguishable from control responses, as described by others (Millecchia and Mauro, 1969a).…”
Section: Pkc Inhibitors Do Not Antagonize Light Adaptationsupporting
confidence: 57%
“…The ease of penetrating these cells with intracellular microelectrodes and the simplicity of their structure have made them a good model system for studying the initial steps of the transduction of light by a receptor into an electric current. Millecchia and Mauro (1969) have shown that discrete waves can also be observed in the ventral nerve receptor. In this paper it will first be shown that for the ventral receptor Eq.…”
mentioning
confidence: 98%